Prevalence and antimicrobial resistance profiles of bacterial pathogens associated with subclinical mastitis and dairy farm environments - Ozbey, G.; Tanriverdi, E. S.; Zigo, F. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2025)
This study investigated the prevalence and antimicrobial resistance (AMR) profiles of bacterial pathogens linked to subclinical mastitis in dairy cows, as well as their occurrence in milk, faecal, and environmental samples collected in eastern Turkey between February and May 2024. A total of 2,400 milk samples were collected from 600 cows affected with subclinical mastitis, along with 292 rectal faecal samples, 150 raw milk samples consumed by the public, and hand and fecal samples obtained from animal breeders in 25 cattle enterprises. In addition, environmental samples such as water, soil, feed, and bedding (five samples per enterprise), were collected. Bacterial isolates cultured from all samples were identified using Matrix-Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) mass spectrometry. Of the 600 cows examined, 292 (48.6%) were CMT-positive, and bacterial growth was detected in 261 (89.7%) of these samples. The predominant isolates were coagulase-negative staphylococci (CoNS, 30.8%), Staphylococcus aureus (19.5%), Escherichia coli (8.9%), and Aerococcus viridans (5.8%). Antimicrobial susceptibility of S. aureus and CoNS against 15 antibiotics and E. coli against 17 antibiotics was assessed using the disc diffusion method, and the mecA gene was screened by PCR. Among 121 E. coli isolates, no mcr, carbapenemase, or beta-lactamase genes were detected by multiplex PCR. Tetracycline resistance was highest among E. coli isolates, particularly in milk samples from mastitic cows, rectal fecal samples, unpasteurised cow's milk, farmer's feces, soil, and feed, while resistance to amikacin, cefepime, cefoxitin, cephalexin, ertapenem, and norfloxacin remained lower. No resistance was observed against kanamycin. The mecA gene was identified in three S. aureus isolates (3/57, 5.3%): two from cows affected with subclinical mastitis and one from a farmer's hand. These findings highlighted the prevalence of major bacterial pathogens, potential therapeutic challenges and public health risks associated with the presence of AMR bacteria and raw milk consumption.
Keywords: one health; Escherichia coli; MALDI-TOF MS; mcr genes; mastitis; Staphylococcus aureus